Pengurusan Izin Bongkar Muat Kapal Asing di Luar Kawasan Pabean Pada Kantor Bea Dan Cukai Oleh PT. Bahari Eka Nusantara - Budi Setiawan; Suratni Ginting; Aja Avriana Said (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The process of obtaining permission to load and unload foreign vessels outside the customs area at the Customs and Excise Office. The implementation of loading and unloading outside the customs area must have permission from the party concerned because the implementation of loading and unloading of foreign ships outside the customs area without permission from the party concerned is a criminal offense which is regulated in Article 10 letter (b) of Law No.17 of 2006 concerning customs. The existence of congestion at the port so that the ship is docked outside the customs area with certain conditions. The need for coordination and thoroughness in processing loading and unloading permits outside the customs area so that all implementations are carried out properly. The task of PT Bahari Eka Nusantara Belawan Branch in licensing loading and unloading outside the customs area is very important because through PT Bahari Eka Nusantara Belawan Branch is the party responsible for the ship that will dock outside the customs area that it agents. Based on the results of the discussion, it can be concluded that there are still obstacles caused by a lack of understanding in the Sibela system input procedure. The late submission of loading and unloading permits outside the customs area is an obstacle to the delay in approval of loading and unloading permits for foreign ships outside the customs area.